Frankie Muse Freeman, Esquire: The Legacy Of The First Female United States Commissioner Of Civil Rights And Presidential Scholar Commissioner - Hon. Nicole Colbert-Botchway (Washington University Journal of Law and Policy, 2022)
Fondly called Frankie ‘Freedom,’ Frankie Freeman was a life-long champion of civil rights. Among her many achievements, Freeman was the first woman appointed to the United States Commission on Civil Rights. In this Article Judge Colbert-Botchway discusses Commissioner Freeman and illustrates how her work was instrumental in fulfilling the promise of equal justice for all. Commissioner Freeman served as lead counsel in several important civil rights cases and was named to the United States Commission on Civil Rights in 1964. She was the first woman and the first person of color to be appointed to the Commission. Although others placed limits on her aspirations, Commissioner Freeman distinguished herself in the legal profession through her fearless service to others and dedicated her life to eliminating the negative consequences of racial inequality, advancing the civil rights movement, and breaking down barriers to equal justice.
Keywords: Frankie Muse Freeman